UNDERSTANDING COOPERATIVE FINANCE AS A NEW COMMON. (30th January 2017) - PÉRILLEUX, Anaïs; NYSSENS, Marthe
ABSTRACT: The emerging field of common good socio‐economics is promising not only for the preservation of common natural resources but also for common goods created by people through collective action, the importance of which has been emphasized by the recent financial and economic crisis. Based on the case of cooperative finance, this paper's outcomes are twofold. First, it shows that while the boundaries between the nature and property regime of goods may be relatively clear for natural common goods, they appear much more interlinked for human‐made goods, where commons are embedded in intergenerational reciprocity. Second, it demonstrates that financial cooperatives can be understood as human‐made commons and proposes a new way of thinking about public policies to design adequate legislation to protect these commons from isomorphism, privatization and destruction.